Artificial intelligence in education: implications for academic integrity and the shift toward holistic assessment - Ateeq, Ali; Alzoraiki, Mohammed; Milhem, Marwan; Ateeq, Ranyia Ali (Frontiers in Education, 2024)
This study examines the impact of Artificial Intelligence (AI) on the field of education, with particular focus on its implications for academic integrity and the adoption of comprehensive assessment approaches. This research fits within the specific setting of university students and faculty members in the Kingdom of Bahrain. Methods: A cross-sectional survey was designed to examine the impact Artificial Intelligence (AI) in field of education, with particular focus on its implications for academic integrity and the adoption of comprehensive assessment approaches. A total of 218 participants were randomly selected from 250 employed in this survey study. Results: Out of 250 invited participants, 203 responded to the survey. This study evaluated the influence of Educational Impact (EI), Policy and Ethics (PE), and Pedagogical Implications (PI) on Academic Outcomes (AO). Results revealed a significant association between EI → AO with a beta of 0.490, t-value of 4.504, and p<0.001. PI also showed a significant relationship (β=0.454, t=2.330, p=0.010) with more variability. PE's impact on AO was modest (β=0.243, t=1.977, p=0.024). Overall, EI was the strongest AO predictor. The R² value was approximately 39%, indicating a good fit.The research reveals a strong link between the Educational Impact (EI) of AI and academic success in Bahrain's universities, with EI being the primary predictor. Both policy and ethics (PE) and pedagogical implications (PI) play crucial roles in this relationship.